Die königlichen Frauen der III. Dynastie von Ur - Weiershäuser, Frauke (Universitätsverlag Göttingen, 2008)
The kings of the III. Dynasty of Ur (2112-2004 BC) were always married with several women at a time, of which only one woman took the position of a queen. Among the large number of economic documents of that period, which give a detailed insight into the state economy and administration, more than 1,000 articles relating to transactions of the royal consorts can be assigned. All women of the rulers of Ur were active in business and administration, they were involved in the cult on several occasions and involved in the complex structures of court life. This work investigates in the sources in which functions and activities the royal women were involved and by which degree the posts of a Queen of Ur were different from that of a concubine. In four discurses the situation of the royal women of the Ur III period is compared with the women of the ruling houses in Ebla and the Early Dynastic Akkade (Akkadezeit).